Solusi Persamaan Burgers Inviscid dengan Metode Pemisahan Variabel - Ihsan, Hisyam; Side, Syafruddin; Iqbal, Muhammad (Jurusan Matematika FMIPA UNM, 2021)
This study examines the solution of Burgers Inviscid equation with variable separation method. The purpose of this study was to find out the simplification of the Navier-Stokes equation system into the Burgers Inviscid equation, find a solution to the Burgers Inviscid equation with the variable separation method, and simulate equation solutions using Maple18 software. The Burgers equation emerged as a complicated simplification of the Navier-Stokes equation system. The Burgers equation is a partial differential equation of conservation law and is a hyperbolic problem, i.e. the simplest nonlinear representation of the Navier-Stokes equation. The variable separation method is one of the classic methods that is effectively used in solving partial differential equations assuming to obtain the x and t components. Then there will be substitutions to differential equations, so that in this way there will be a partial differential equation solution.